2021
DOI: 10.1021/acs.jafc.1c04064
|View full text |Cite
|
Sign up to set email alerts
|

Novel Citral-thiazolyl Hydrazine Derivatives as Promising Antifungal Agents against Phytopathogenic Fungi

Abstract: To develop new antifungal agents against phytopathogenic fungi, a series of citral-thiazolyl hydrazine derivatives were designed, synthesized, and characterized by FT-IR, 1 H NMR, 13 C NMR, and HRMS. Antifungal activity results showed that most synthetic compounds exhibited broad-spectrum antifungal activities against six phytopathogenic fungi in vitro. Notably, compounds b and c15 exhibited remarkable antifungal activity against Colletotrichum gloeosprioides, Rhizoctonia solani, Phytophthora nicotianae var. n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 36 publications
2
25
0
Order By: Relevance
“…In contrast, the hyphae of the untreated control group showed a smooth surface and normal growth ( Figure 4 a). Together with previous research findings [ 40 , 41 ], we speculate that the fungal cell walls and cell membranes of T. versicolor are potential targets of the camphor derivatives, but the mechanism of action of camphor derivatives needs further study.…”
Section: Resultssupporting
confidence: 84%
“…In contrast, the hyphae of the untreated control group showed a smooth surface and normal growth ( Figure 4 a). Together with previous research findings [ 40 , 41 ], we speculate that the fungal cell walls and cell membranes of T. versicolor are potential targets of the camphor derivatives, but the mechanism of action of camphor derivatives needs further study.…”
Section: Resultssupporting
confidence: 84%
“…This result indicates that fluorine atom substitution of the meta-position could reinforce the antifungal activities of citral-thiourea compounds, which supports findings reported by previous research. 15,36 These results indicate that there exists close contact between the electronic and steric effects of substituent groups and the biological properties of citral-thiourea derivatives. 37,38 In Vivo Antifungal Effects of Derivatives against C. gloeosporioides.…”
Section: ■ Materials and Methodsmentioning
confidence: 76%
“…To this end, botanical fungicides prepared by pinene, camphor, citral, and so on have recently garnered much attention in the field of pesticide research. Among these, citral, the main component of Litsea cubeba essential oil, is considered the most promising of the fungicides due to having the properties of broad-antifungal activity, low toxicity, and easy modification. To screen for citral-based derivatives that feature high antifungal activity, current research focus has increasingly shifted toward the synthesis of citral-based derivatives. He et al researched the antifungal effects of synthetic citral-based 1,2,3-triazole compounds against phytopathogenic plant fungi and found that the inhibition rate of these compounds against Colletotrichum orbiculare reached 95.2% at the concentration of 50 mg/L.…”
Section: Introductionmentioning
confidence: 99%
“…Rice plants with consistent growth at the end of tillering were chosen for the in vivo antifungal activity test. 18 To test the curative effect, activated R. solani was inoculated into the rice and cultivated for 24 h before being sprayed with 6a 5 , 6a 19 , and trifloxystrobin at concentrations of 200, 100, and 50 μg/mL, respectively. Distilled water containing 0.02% Tween 80 was set as a blank control.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Rice plants with consistent growth at the end of tillering were chosen for the in vivo antifungal activity test . To test the curative effect, activated R.…”
Section: Methodsmentioning
confidence: 99%